2014
DOI: 10.1038/nature13666
|View full text |Cite
|
Sign up to set email alerts
|

Nodal signalling determines biradial asymmetry in Hydra

Abstract: In bilaterians, three orthogonal body axes define the animal form, with distinct anterior-posterior, dorsal-ventral and left-right asymmetries. The key signalling factors are Wnt family proteins for the anterior-posterior axis, Bmp family proteins for the dorsal-ventral axis and Nodal for the left-right axis. Cnidarians, the sister group to bilaterians, are characterized by one oral-aboral body axis, which exhibits a distinct biradiality of unknown molecular nature. Here we analysed the biradial growth pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 30 publications
4
124
0
Order By: Relevance
“…The rangeomorphs appear to have one main body axis and one lateral branching axis, an arrangement very similar to various cnidarian organisms (Watanabe et al ., 2014), with which they also share developmental similarities, i.e. a conserved form and potential positioning of the generative zone.…”
Section: Implications For Developmental Evolutionmentioning
confidence: 99%
“…The rangeomorphs appear to have one main body axis and one lateral branching axis, an arrangement very similar to various cnidarian organisms (Watanabe et al ., 2014), with which they also share developmental similarities, i.e. a conserved form and potential positioning of the generative zone.…”
Section: Implications For Developmental Evolutionmentioning
confidence: 99%
“…Nodal also has a role during later embryogenesis of sea urchins, where it breaks symmetry even though adult sea urchins are radially-symmetrical [40]. In fact, recent research by Watanabe et al [41] has shown that a Nodal-related gene has a role in determining a structural axis in the radially-symmetrical Cnidarian, Hydra: it establishes a body axis for a new bud distinct from that of the parent. Given these roles of Nodal in the development of structural asymmetry [42], asymmetry in invertebrates and vertebrates may have at least some homologous aspects.…”
Section: What Is the Relationship Between Asymmetry In Invertebrates mentioning
confidence: 99%
“…Wnt, BMP and Nodal represent the signaling pathways defining the body axes during embryonic development, at least in bilaterians. These pathways were possibly present in the most recent common ancestor of all metazoans (reviewed in Holstein et al, 2011) and their involvement in whole body or body structure re-patterning has been reported in cnidarians, acoel, platyhelminthes, and deuterostomes (Holstein et al, 2003;Yakushiji et al, 2009;Adell et al, 2010;Reddien, 2011;Srivastava et al, 2014;Watanabe et al, 2014).…”
Section: Morphogenetic Events In Regenerationmentioning
confidence: 99%